Dendrimers as nanoscale vectors: Unlocking the bars of cancer therapy. (November 2022) - Dey, Asmita Deka; Bigham, Ashkan; Esmaeili, Yasaman; Ashrafizadeh, Milad; Moghaddam, Farnaz Dabbagh; Tan, Shing Cheng; Yousefiasl, Satar; Sharma, Saurav; Maleki, Aziz; Rabiee, Navid; Kumar, Alan Prem; Thakur, Vijay Kumar; et al.
Abstract: Chemotherapy is the first choice in the treatment of cancer and is always preferred to other approaches such as radiation and surgery, but it has never met the need of patients for a safe and effective drug. Therefore, new advances in cancer treatment are now needed to reduce the side effects and burdens associated with chemotherapy for cancer patients. Targeted treatment using nanotechnology are now being actively explored as they could effectively deliver therapeutic agents to tumor cells without affecting normal cells. Dendrimers are promising nanocarriers with distinct physiochemical properties that have received considerable attention in cancer therapy studies, which is partly due to the numerous functional groups on their surface. In this review, we discuss the progress of different types of dendrimers as delivery systems in cancer therapy, focusing on the challenges, opportunities, and functionalities of the polymeric molecules. The paper also reviews the various role of dendrimers in their entry into cells via endocytosis, as well as the molecular and inflammatory pathways in cancer. In addition, various dendrimers-based drug delivery (e.g., pH-responsive, enzyme-responsive, redox-responsive, thermo-responsive, etc.) and lipid-, amino acid-, polymer- and nanoparticle-based modifications for gene delivery, as well as co-delivery of drugs and genes in cancer therapy with dendrimers, are presented. Finally, biosafety concerns and issues hindering the transition of dendrimers from research to the clinic are discussed to shed light on their clinical applications. Graphical Abstract: ga1